THE LIFE AND ACTIVITY OF THE POET HOJA ISMAT, WHO LIVED AND CREATED IN THE TEMURIAN PERIOD - Shukurov Foziljon Makhmadovich, (EPRA International Journal of Research and Development (IJRD), 2022)
In this article is written about the life and work of the poet Ismat Bukhariy, who lived and worked in the second half of the 14th century and the beginning of the 15th century, the composition and content of his poems. For many years, the poet's work has attracted the attention of famous literary critics. An in-depth study of the poet's poems is one of the most relevant topics today.